Eksplorasi Respon, Koping Dan Adaptasi Pasien Kanker Yang Sedang Menjalani Kemoterapi Selama Masa Pandemi Covid-19 : Studi Fenomenologi - Hendra Dwi Cahyono; Ina Martiana (NHM PRESS, 2022)
Background: The pandemic condition poses two main health risks for cancer, namely interrupted care (treatment process, radiotherapy, surgery) and increased cancer susceptibility to COVID 19. In primary care facilities, there are delays in diagnosis, and cancer. Reluctance to refer suspected cancer to secondary care. Purpose: taking an in-depth picture of the response, decision making and adaptation of patients who are undergoing the Covid-19 pandemic Method: a phenomenological approach, to explore respondent information about the response, coping and adaptation of patients who are undergoing the Covid-19 pandemic. This research was conducted in the Chemotherapy Unit room at Baladhika Husada Hospital Jember in December 2021 with a total of 11 respondents who were selected through purposive sampling. Data was collected by means of semi-structured interviews which were recorded using a voice recorder. Results: four themes, namely obstacles in treating patients that have an impact on treatment, respondents' expectations in dealing with cancer experienced and the covid-19 pandemic, Dilemmas against Covid-19, and Anxiety if respondents do not do chemotherapy. Conclusion: Adjustment of cancer care during the COVID-19 pandemic requires a solid collaboration in order to jointly solve the Covid-19 problem. Expectations are always the respondent's reinforcement, played by environmental and family factors as an adaptive support system.